Hidroponics in a Senior University: fundamentals of a different method for plant growth - Lima, Ivo M. (2017)
[Excerpt] Communicating science in a tangible, clear and simple way is crucial for the preparation of a scientifically informed and collectively clarified society, capable of keeping along with the needs of a time where technology grows at a dizzying speed and dealing with the enormous amount of handy information about almost everything. Briefly, Science Communication is to share ideas about possible complex themes in a simple way with a public usually unaware of the matter (Grossman, 2014). Nowadays, the search for knowledge by an increased number of enthusiastic people, thrilled about several science fields, it is quite notorious. But also, no matter the age or educational qualifications, people are more and more capable of browsing information in the web that may help them finding answers to their everyday life problems (health, social, economic, legal, etc.). The technological and scientific progress witnessed in the last century have led to a better life quality, as well as an increased in average life time (Almeida et al., 2012). At the same time, there is a worldwide increase in senior population, each time with a higher level of education. This means that it is required the recognition and reapproval of this senior knowledge (Machado and Medina, 2012), maintaining their viability and ensuring that they participate in the society (Almeida et al., 2012), which in turn widens the possibilities of this amazing people eager to learn. [...]